2017
DOI: 10.1007/s11356-017-0090-3
|View full text |Cite
|
Sign up to set email alerts
|

Fine particle matters induce DNA damage and G2/M cell cycle arrest in human bronchial epithelial BEAS-2B cells

Abstract: There is compelling evidence that exposure to particulate matter (PM) is linked to lung tumorigenesis. However, there is not enough experimental evidence to support the specific mechanisms of PM-induced DNA damage and cell cycle arrest in lung tumorigenesis. In this study, we investigated the toxic effects and molecular mechanisms of PM on bronchial epithelial (BEAS-2B) cells. PM exposure reduced cell viability and enhanced LDH activity. The cell growth curves of BEAS-2B cells decreased gradually with the incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 56 publications
1
25
0
Order By: Relevance
“…In addition, the indoor PM 2.5 exposure levels were positively associated with skin aging manifestation, including score of pigment spots on forehead and wrinkle on upper lip [ 140 ]. PM 2.5 may lead to induced DNA damage and cell cycle arrest in lung tumorigenesis [ 141 ]. Repeated exposure to PM 2.5 induces vascular inflammation [ 142 ].…”
Section: Various Impacts Of Pm 25 Pollutionmentioning
confidence: 99%
“…In addition, the indoor PM 2.5 exposure levels were positively associated with skin aging manifestation, including score of pigment spots on forehead and wrinkle on upper lip [ 140 ]. PM 2.5 may lead to induced DNA damage and cell cycle arrest in lung tumorigenesis [ 141 ]. Repeated exposure to PM 2.5 induces vascular inflammation [ 142 ].…”
Section: Various Impacts Of Pm 25 Pollutionmentioning
confidence: 99%
“…Bronchial epithelial cells line the respiratory airways and are the first cells of the lung exposed to PM 2.5 . Studies of bronchial epithelial cells directly exposed to PM 2.5 have shown that PM 2.5 impairs bronchial epithelial cell function (Zhang et al, 2017), causes mitochondrial dysfunction (Lavrich et al, 2018), and at high doses, induces cell toxicity and death (Dergham et al, 2015; Wu et al, 2017). PM 2.5 has also furthermore been shown to induce bronchial epithelial cells to synthesize proinflammatory cytokines, including interleukin (IL)-6, IL-8, and tumor necrosis factor (TNF)-α (Ovrevik et al, 2009; Wang et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Here, we found that PM exposure induces cell cycle arrest in maturing oocytes by blocking the degradation of cyclin B1. Similarly, evidence regarding alteration of cell cycle by PM exposure also supports the PM-induced arrest of G2/M phase and regulation of spindle organization (Longhin et al, 2013;Wu et al, 2017). Therefore, exposure to PM can arrest oocyte maturation at the metaphase stage and may regulate maturation such as spindle organization.…”
Section: Discussionmentioning
confidence: 83%